Hubungan Inovasi Sosial dengan Keberlanjutan Usaha Mahasiswa Universitas Negeri Medan di Bidang Ekonomi Kreatif - Fikri Alfahmi Siregar; Alexander Sabastian Pangaribuan; Azri Nuansa Indah Nasution; Aulia Ramadhani; Nabila Umaira; Saidun Hutasuhut (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the relationship between social innovation and business sustainability among student entrepreneurs at Universitas Negeri Medan who are engaged in the creative economy sector. The research was conducted using a quantitative survey approach with 100 respondents selected through simple random sampling. Data were collected using a structured questionnaire and analyzed through a series of statistical tests, including validity, reliability, normality, and Pearson correlation analysis. The results indicate that all questionnaire items met the validity and reliability criteria, and the data were normally distributed. The correlation analysis further shows a positive and significant association between social innovation and business sustainability. These findings suggest that students who are able to introduce creative solutions, refine service processes, and adapt their business practices to social needs tend to achieve higher levels of sustainability. The study emphasizes that social innovation contributes not only to competitive advantage but also to the long-term resilience of student-led creative businesses.